Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1159/000095488
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations of Diabetes Mellitus

Abstract: Objective: To study the prevalence of cutaneous disorders in patients with diabetes mellitus. Subjects and Methods: All diabetic patients attending the Department of Dermatology, Al-Farwaniya Hospital, Kuwait, and diabetic in-patients with skin disorders were examined over a period of 18 months from March 2004 to August 2005. A total of 106 diabetic patients displaying 1 or more dermatological manifestations were identified and thoroughly examined for any skin disorder. The diabetic profile of the patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
4
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 11 publications
6
31
4
1
Order By: Relevance
“…There was a statistically significant (p ! 0.001) difference in skin manifestations between our type 1 and type 2 DM patients, contrary to the finding in other studies [7,15,17] . Most of the patients (71%) with type 1 diabetes in our study had a brief duration of diabetes (group I).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There was a statistically significant (p ! 0.001) difference in skin manifestations between our type 1 and type 2 DM patients, contrary to the finding in other studies [7,15,17] . Most of the patients (71%) with type 1 diabetes in our study had a brief duration of diabetes (group I).…”
Section: Discussioncontrasting
confidence: 99%
“…Cutaneous infections (38.4%) comprised the second most frequent manifestation seen in our patients, similar to previous reports [14,17] . Fungal infections (28.1%) were among the most frequent cutaneous infec- tions, and tinea pedis (21.9%) was most frequent among fungal infections, a finding similar to that of a previous study [19] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3 Al-Mutairi et al looked at the prevalence of cutaneous manifestations in 106 patients with diabetes mellitus: pruritus was shown to be the second most common cutaneous manifestation, with 49% of patients affected. 4 A study in elderly subjects showed diabetes to be a statistically significant predictor of pruritus. 5 In contrast, one study showed that generalised pruritus of unknown cause was especially common in people with diabetes (8/300 patients), but pruritus vulvae was significantly more common in women with diabetes (18.4%) compared with 100 non-diabetic controls (5.6%) and was strongly associated with poor diabetic control.…”
Section: Introductionmentioning
confidence: 99%